Analysis of Special Allocation Funds on Economic Growth in North Sulawesi Province - Tampil, Velicia Criselda; G. Kumenaung, Anderson; Kawung, George (Journal of Indonesian Scholars for Social Research, 2022)
As many other nations, Indonesia has been widely impacted by the Covid 19 Pandemic which not only affected the wellbeing of the people but also it has seeped into the nation’s financial policies. The aim of this writing is to examine how Special Allocation Fund in health and agriculture affects overall economic performance of Sulawesi Utara Province of which extensive research needs to be undertaken. This research utilizes Multiple Linear Regression analysis method on time series data throughout 2012 – 2020 fiscal period. The data sources for this research are Sulawesi Utara Accounting Department Office and Sulawesi Utara Central Bureau of Statistics. Our research suggests that the Special Allocation Funds in health has significant and positive impact on the economic growth whereas Special Allocation Funds in agriculture sector has less impact on the overall economic growth. However, the composite impact of both Special Allocation Funds in economic performance of Sulawesi Utara Province is noticeable.